1995
DOI: 10.1007/bf03349688
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of μ-opioid receptors in the modulation of pituitary-adrenal axis in normal and stressed rats

Abstract: The availability of the most selective, high-affinity, natural opioid agonists for mu-receptors (dermorphin-DM) and delta-receptors (deltorphin-DT) has provided the possibility for in vivo studying of the role of acute and chronic activation of mu- and delta-opioid receptors on the functional activity of the hypothalamus-pituitary-adrenocortical (HPA) axis, both in basal conditions and in response to an acute stress in adult male rats. Plasma corticosterone (CS) and beta-endorphin-like-immunoreactivity (beta-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
1
28
0
1
Order By: Relevance
“…We have now shown that, in pregnancy, the enhancing action of endogenous opioid on ACTH release in response to forced swimming, which is normally seen in virgins, is removed. The reduction in ACTH secretion in response to the stressor after naloxone in virgins is consistent with the findings of previous studies showing that opioid antagonists reduce ACTH and corticosterone secretion in response to a stressor in male rats (degli Uberti et al 1995). Naloxone is likely to be exerting its effects on the HPA axis via the hypothalamus (Wang et al 1996), and thus may affect hypothalamic-pituitary mechanisms through CRH release.…”
Section: Endogenous Opioids and Stress In Pregnancy · A J Douglas Andsupporting
confidence: 91%
“…We have now shown that, in pregnancy, the enhancing action of endogenous opioid on ACTH release in response to forced swimming, which is normally seen in virgins, is removed. The reduction in ACTH secretion in response to the stressor after naloxone in virgins is consistent with the findings of previous studies showing that opioid antagonists reduce ACTH and corticosterone secretion in response to a stressor in male rats (degli Uberti et al 1995). Naloxone is likely to be exerting its effects on the HPA axis via the hypothalamus (Wang et al 1996), and thus may affect hypothalamic-pituitary mechanisms through CRH release.…”
Section: Endogenous Opioids and Stress In Pregnancy · A J Douglas Andsupporting
confidence: 91%
“…Endogenous and exogenous opioids are also known to affect the hypothalamicpituitaryadrenocortical axis (HPA) with contrasting effects depending on the administration mode (acute cfchronic). For example, acute administration of morphine, to activate p-opioid receptors, increases the release of neurohormones, like corticosterone, from the HPA axis [38]. In contrast, chronic treatment with tx-opioid agonists results in a decreased responsiveness of the HPA axis to stress in rats (for review see [39]).…”
Section: Discussionmentioning
confidence: 99%
“…Opioid analgesics and endogenous opioid peptides have a wide range of physiological and behavioral effects on pain perception, motivation, locomotion, regulation of intestinal motility, immunomodulation, thermo-regulation, neuroendocrine secretion, and rewarding effects (Pasternak, 1988;Mansour et al, 1988;Cahill et al, 2001). It is well known that endogenous opioid peptides are released in the central nervous system in response to stressful stimuli, and activation of m-opioid receptor plays an important role in stressful conditions (Kiritsy-Roy et al, 1986;degli Uberti et al, 1995). d-Opioid receptors have also been associated with anxiety and depression, since d-agonists reduced the immobility of rats in a forced swimming test (Broom et al, 2002).…”
Section: Introductionmentioning
confidence: 99%